Strengthening Family Institution through Pre-Marital Course: Comparative Study between Indonesia and Malaysia - Bidayati, Kholis; Jahar, Asep Saepudin; Yasin, Yuli (Fakultas Syariah UIN Sulthan Thaha Saifuddin Jambi, Indonesia, 2020)
This study examines the policy of premarital course in Indonesia and Malaysia. The premarital course aims to equip the bride and groom with the knowledge and skills of making good family besides attempting to reduce the high rate of divorces in both countries. Premarital course conducted by BP4 Institutions in Indonesia and JAKIM in Malaysia applied different approaches and policies. This study tries to elaborate pre-marital course in Indonesia and Malaysia by examining policies and substantial issues. The data was collected through library research, examining regulations and rules applied in both countries. This study showed that the procedure and mechanism of premarital course in Indonesia and Malaysia were different. Premarital course in Malaysia is mandatory and one of the requirements of marriage registration document whereas in Indonesia is voluntary. Both countries, however, applied a similarity approach and strategy in delivering course materials.